Paradoxical spinopelvic motion: does global balance influence spinopelvic motion in total hip arthroplasty? - Yu-Hsien Lin; Yu-Tsung Lin; Kun-Hui Chen; Chien-Chou Pan; Cheng-Min Shih; Cheng-Hung Lee (BMC Musculoskeletal Disorders, 2021)
Abstract Background Recent research has proposed a classification of spinopelvic stiffness according to pelvic spatial orientation for risk stratification in patients who undergo total hip arthroplasty (THA). However, the influence of global alignment was not investigated, and this study evaluated the effect of global balance (sagittal vertical axis [SVA]) on spinopelvic motion. Methods We conducted a retrospective review of consecutive primary THA patients. We measured SVA, spinopelvic parameters (pelvic tilt [PT], pelvic incidence, and sacral slope), thoracic kyphosis (TK), lumbar lordosis (LL), proximal femur angle (PFA), and cup version using functional radiographs of patients in the standing and upright sitting positions. Linear regression was performed to identify parameters related to global trunk alignment change (∆SVA). Spinopelvic stiffness was defined as PT position change < 10°, and a subset of patients with PT change < 0° was categorized into a paradoxical spinopelvic motion group. Results One hundred twenty-four patients were analyzed (mean age: 65 years, 61% female). In univariate regression analysis, ∆TK, ∆LL, and ∆PFA were correlated to ∆SVA. In multivariate regression analysis, ΔLL (p < 0.001) and ΔPFA (p < 0.001) were found to be correlated to ΔSVA (ΔSVA = − 11.97 + 0.05ΔTK – 0.23ΔLL – 0.17ΔPFA; adjusted R2 = 0.558). Spinopelvic stiffness was observed in 40 patients (32%), including five (4%) with paradoxical motion (∆PT = − 3° ± 1°, p < 0.001) with characteristics of balanced standing global trunk alignment (standing SVA = − 1.0 ± 5.1 cm), similar stiffness of the lumbosacral spine (∆LL = − 7° ± 5°), higher hip motion (∆PFA = − 78° ± 6°, p = 0.017), and higher anterior trunk shift (∆SVA = 6.2 ± 2.0 cm, p = 0.003) from standing to sitting as compared to the stiffness group. Two of these five patients experienced dislocation events after THA. Conclusions The lumbosacral and hip motions were the major contributors to global alignment postural change. Paradoxical motion is a rare but dangerous clinical condition in THA that might be related to a disproportionally large trunk shift in the stiff lumbosacral spine causing excessive hip motion. In paradoxical motion, diminishing functional acetabular clearance during position change might pose the prosthesis at higher risk of impingement and instability than spinopelvic stiffness.